2023
DOI: 10.1126/scisignal.ade6737
|View full text |Cite
|
Sign up to set email alerts
|

A virally encoded GPCR drives glioblastoma through feed-forward activation of the SK1-S1P 1 signaling axis

Nick D. Bergkamp,
Jeffrey R. van Senten,
Hendrik J. Brink
et al.

Abstract: The G protein–coupled receptor (GPCR) US28 encoded by the human cytomegalovirus (HCMV) is associated with accelerated progression of glioblastomas, aggressive brain tumors with a generally poor prognosis. Here, we showed that US28 increased the malignancy of U251 glioblastoma cells by enhancing signaling mediated by sphingosine-1-phosphate (S1P), a bioactive lipid that stimulates oncogenic pathways in glioblastoma. US28 expression increased the abundance of the key components of the S1P signaling axis, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Aside from regulating many physiological processes, dysregulated GPCR expression and/or signaling has been linked to several hallmarks of cancer (reviewed in [35] ), including proliferation and survival [36] , invasion and metastasis [37] , angiogenesis [38] , and immune cell evasion [39] . For instance, in breast cancer, the chemokine receptor CXCR4 is overexpressed and its natural ligand, CXCL12, was shown to be highly secreted near the organs that are the metastatic destination of the tumor cells, indicative of a key role in metastatic colonization [37] .…”
Section: G Protein-coupled Receptors and Their Oncomodulatory Propertiesmentioning
confidence: 99%
“…Aside from regulating many physiological processes, dysregulated GPCR expression and/or signaling has been linked to several hallmarks of cancer (reviewed in [35] ), including proliferation and survival [36] , invasion and metastasis [37] , angiogenesis [38] , and immune cell evasion [39] . For instance, in breast cancer, the chemokine receptor CXCR4 is overexpressed and its natural ligand, CXCL12, was shown to be highly secreted near the organs that are the metastatic destination of the tumor cells, indicative of a key role in metastatic colonization [37] .…”
Section: G Protein-coupled Receptors and Their Oncomodulatory Propertiesmentioning
confidence: 99%
“…The human cytomegalovirus-encoded G protein-coupled receptor (GPCR), US28, was reported to promote U251 glioblastoma malignancy by stimulating SPHK1 function to release more S1P, which signals via S1PR1 using in vitro assays ( Figure 4 ). The SPHKI/S1P/S1PR1 signaling activates AKT, JAK2/STAT3, and cMYC and enhances the levels of the cancerous inhibitor of protein phosphatase 2A (CIP2A) downstream to promote the pro-survival phenotype in glioblastoma cells [ 97 ]. Using xenogeneic glioma mouse models and in vitro assays, Arseni et al showed that SPHK1/S1P/S1PR signaling axis consistently stimulates the enhanced recruitment of tumor-associated macrophages (TAMs), triggering pro-tumorigenic phenotype in glioblastoma cells [ 98 ].…”
Section: Sphingolipid Metabolism In Glioblastomamentioning
confidence: 99%